Split Heat Pump Distillation Based on Two‐Stage Compression for Separating an Acetone‐Water Mixture. Issue 1 (4th December 2021) - Yang, Deming; Li, Ming; Lou, Chao; Wan, Dehao; Yun, Yi
Abstract: There is a constant concentration zone for acetone‐water mixtures, and the average relative volatility of the two components in the constant concentration zone is only 1.41, so the energy consumption of the conventional distillation process is high. Two kinds of split mechanical vapor recompression (MVR) heat pump distillation processes, i.e., single‐stage and two‐stage compression processes, were proposed to separate acetone‐water mixtures. The thermodynamic data of the mixture were calculated and modules of Aspen Plus were used to simulate the distillation column and steam compressor. Taking the minimum total annual cost as the objective function, the conventional MVR and the two split MVR heat pump distillation processes were simulated and optimized. Compared with the conventional process, the MVR heat pump distillation process had greater economic advantages, and the split heat pump distillation (SHPD) with two‐stage compression was superior to the other MVR heat pump distillation processes. Abstract : Split mechanical vapor recompression heat pump distillation for acetone‐water mixtures with constant concentration zone is investigated. Four different distillation processes were simulated and discussed. The proposed process had greater economic advantages than the conventional distillation process, so an effective energy‐saving approach for separating acetone and water is introduced.